Menakar Realitas Politik Pencitraan pada Pilgub Ntb 2018: Perspektif Etika Politik Islam - nurjihadi, ahmad (Jurnal Review Politik, 2018)
The focus of this study seeks to answer how imaging politics are played by contestants of governor and deputy governor candidates in the NTB 2018 PILGUB and how to analyze Islamic political ethics against the facts of imaging politics. The character of this research is phenomenalogical research which will unravel political ethics and morality which underlie the existence of political imaging of candidates. The technical analysis used is an analysis of phenomena that try to unravel the facts of imaging politics and measure them by analyzing Islamic political ethics. The results of the study are several trends, namely; first, A and B nominate themselves as the Governor of NTB 2018 even though their tenure has been running for less than 2 years. Second, the phenomenon of women and dynastic political tendencies. Third, the tendency of national politicians to go down the mountain. Fourth, Personafication of Personal Candidates is like a prominent image based on religious (Muslim) integrity. Fifth, Psedo-Populis is a sudden populist phenomenon that is displayed by several candidates. Sixth is Strengthening Communal and Regional Identity such as affiliation with religious organizations, regional sons based on territory and ethnic origin.